Huluran Kasih of back-to-school sets by Sime Darby and Universiti Malaysia Pahang - Irene, Wei Kiong Ting (QS Asia, 2019)
Universiti Malaysia Pahang (UMP) worked with Sime Darby Foundation (SDF) and brought together 300 students from 60 primary and secondary schools in Kuantan and Pekan, Pahang, Malaysia for “Huluran Kasih” (it means love giving/sharing in English), whereby each student received a set of new school uniform, shoes, stockings, school bag, and stationaries at the UMP Pekan campus on 12 December 2018.